Combination of Multi-Attributive Ideal-Real Comparative Analysis and Rank Order Centroid in Supplier Performance Evaluation - Arshad, Muhammad Waqas; Setiawansyah; Mesran; Desyanti (STMIK Budi Darma, 2024)
Supplier performance evaluation is a critical aspect of supply chain management that focuses on assessing and monitoring the performance of suppliers. Supplier performance evaluation not only provides benefits for the company, but also motivates suppliers to improve their quality standards and operational efficiency. This study aims to evaluate supplier performance based on existing assessment data by applying the ROC method to determine the weight of the criteria used, then the MAIRCA method will evaluate supplier performance so that it will produce a rating of supplier performance evaluation which will be a decision recommendation for companies in assessing the performance of existing suppliers. The combination of ROC and MAIRCA weighting methods forms a powerful approach in addressing the complexity and challenges of multi-criteria decision making. ROC with its focus on relative ranking criteria, whereas MAIRCA which considers the difference between ideal and real conditions, presents complementary perspectives. By combining the two, decision makers can generate a more contextual and informational weight of criteria. The ranking result graph in figure 4 shows the best supplier performance obtained on behalf of Supplier C with a final value of 0.052391944 ranked 1, then on behalf of Supplier F with a final value of 0.050077222 ranked 2, and on behalf of Supplier G with a final value of 0.049074028 ranked 3.